THE METHODOLOGY OF DUAL SCALES IN EXPERT ESTIMATING PARAMETERS OF AN INTERMEDIATE EVENTS TREE OF AVIATION ACCIDENT DEVELOPMENT WITH PREVENTION AND PARRYING BARRIERS - A. I. Orlov; Yu. G. Savinov; A. Yu. Bogdanov (Научный вестник МГТУ ГА, 2016)
The new dual methodology of expert estimation of the parameters of intermediate events tree in the development of aviation event / incident is elaborated in the article on the basis of logical and probabilistic model that combines the advantages of both widely used methods FMEA and FTA [1].